The Effectiveness of the Quick Coherence Technique using Heart Rate Variability-Biofeedback Technology on the Recovery of Heart Coherence among University Students - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (Universiti Putra Malaysia, 2018)
Literature has established the effectiveness of self-regulatory techniques using Heart Rate Variability (HRV)-Biofeedback Technology in improving individual’s heart coherence. The current study aims to evaluate the effectiveness of Quick Coherence Technique, a self-regulatory technique, through the application of HRV-biofeedback technology on the level of heart coherence among university students. A total of 20 students of a technical public university participated in the study. The Quick Coherence Technique (QCT) and the emWave device and software of the HeartMath Institute were used to collect the data. According to the HRV power spectrum, the HRV data is divided under very low frequency (VLF), low frequency (LF), and high frequency (HF) frequency ranges. Based on the results, the use of HRV-biofeedback technology and the QCT had helped to increase the levels of HRV scores and heart coherence of the participants.